Praia da Almada, Ubatuba, SP: um berçário para a ictiofauna - Fernandes, Nathalie Amorim (2016)
Beaches of the city of Ubatuba are known for their high number of endemic fish species and are characterized as an important spawning area for many fishes from distinct oceanic zones. Many of the beaches in the region have sandy bottom, a feature that makes them dynamic environments with a great variety of marine species. The surf zone ichthyofauna of sandy beaches of the state of São Paulo is still little studied, and there aren’t many published works on the subject. The present study aimed to survey the structure of the ichthyofauna present in the surf zone of Praia da Almada in the seasonal, circadian and spatial contexts, as well as to verify its importance as a nursery. Diurnal and nocturnal samples were collected seasonally at each collection point along the beach for two years. Salinity, water and air temperatures were also measured. Fish were identified at the lowest possible taxonomic level, weighed and measured. Data were grouped by season, period (day or night) and point of collection for analysis of the seasonal, circadian and spatial variations. A total of 1483 individuals from 30 species and 13 families were collected. Menticirrhus littoralis, Trachinotus carolinus, Umbrina coroides, Trachinotus goodei, Atherinella brasiliensis and Atherinella blackburni were considered very common in relation to the relative frequency of occurrence, with the former three being the most abundant in the study. Although abundant and constant, A. brasiliensis is classified as endangered in the state of São Paulo, and its abundance in Praia da Almada indicates that this species seems to find refuge in this beach of Ubatuba. Other species showed seasonal occurrence, such as Engraulis anchoita and Hyporhamphus unifasciatus, which occurred exclusively in fall. The highest values of the Margalef Diversity Index (DMg) were recorded in the fall. Winter was the least abundant season and with greater dominance, while summer was the most abundant. The total biomass was 5044.88 g, almost 40% of which concentrated in spring, while winter presented the lowest biomass. There are slightly more species at night than in the day, but without conspicuous variations in abundance and biomass. One of the main results of this work is the confirmation that the surf zone of this type of beach serves as refuge and nursery for many species of fish, due to the expressive amount of juvenile found.